2002
DOI: 10.1002/art.10183
|View full text |Cite
|
Sign up to set email alerts
|

Local production of complement proteins in rheumatoid arthritis synovium

Abstract: Conclusion. In summary, local complement production and activation may play an important role in RA, and specific modulation and inhibition of local complement production could be an attractive therapeutic target for RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 46 publications
5
110
0
1
Order By: Relevance
“…Uncontrolled activation of this system, however, can seriously damage host cells and tissues and contribute significantly to disease progression (178)(179)(180)(181). Activated components of the alternative pathway, for example, have been described in the pathology of glomerulonephritis, IgA nephropathy, asthma, lupus, rheumatoid arthritis, myositis, inflammatory central nervous system diseases like multiple sclerosis, cardiac valvular disease, cirrhosis, adult respiratory distress syndrome (ARDS), pemphigoid disease, and antiphospholipid syndrome (182)(183)(184)(185)(186)(187)(188). Thus, because of its spontaneous activating properties, continuous control of the alternative pathway is necessary to prevent damage to self tissues.…”
Section: The Complement System and Amdmentioning
confidence: 99%
“…Uncontrolled activation of this system, however, can seriously damage host cells and tissues and contribute significantly to disease progression (178)(179)(180)(181). Activated components of the alternative pathway, for example, have been described in the pathology of glomerulonephritis, IgA nephropathy, asthma, lupus, rheumatoid arthritis, myositis, inflammatory central nervous system diseases like multiple sclerosis, cardiac valvular disease, cirrhosis, adult respiratory distress syndrome (ARDS), pemphigoid disease, and antiphospholipid syndrome (182)(183)(184)(185)(186)(187)(188). Thus, because of its spontaneous activating properties, continuous control of the alternative pathway is necessary to prevent damage to self tissues.…”
Section: The Complement System and Amdmentioning
confidence: 99%
“…Reduced levels of native complement components and increased levels of complement metabolites in the synovial fluid and synovial tissue of RA patients have implicated complement in the pathogenesis of RA (16). It has been suggested that key components in complement activation, such as C3 and B, are produced locally in RA synovium rather than being plasma derived (17). Aggarwal et al recently demonstrated alternative pathway activation with formation ofthe membrane attack complex in patients with juvenile rheumatoid arthritis (18).…”
Section: Complement and Autoantibodiesmentioning
confidence: 99%
“…Deposited autoantibodies, immune complexes, apoptotic cells, and necrotic cells can activate this cascade, leading to the release of proinflammatory activators, recruitment of inflammatory cells (Figure 1), and formation of membrane attack complexes. The levels of complement activation components are elevated in the synovial fluid, synovium, and cartilage of patients with arthritis (19)(20)(21)(22)(23), and targeted deletion/inhibition reduces disease severity in murine arthritis models (7,24,25). These previous studies have led to the development of therapeutic approaches targeting complement components for the treatment of RA (for review, see ref.…”
Section: Complement Cascadementioning
confidence: 99%